Distribution of Diphtheria Cases by Population Density and Access to Health Centers in East Java Province, 2022–2024 - Nailah Husna Salsabila (International Journal of Health Engineering and Technology, 2026)
Diphtheria remains a re-emerging public health threat in Indonesia, with East Java Province consistently reporting the highest national case burden. This study aimed to describe the spatial distribution of diphtheria cases in relation to population density and healthy home coverage across all 38 districts and cities of East Java Province from 2022 to 2024. An ecological study design with a temporal-spatial approach was employed using secondary data sourced from the East Java Provincial Health Profile for the period 2022–2024. Data were analyzed and visualized using Quantum GIS version 3.34.3 through choropleth and spatial overlay mapping techniques. A total of 909 diphtheria cases were recorded over the study period, with annual increases culminating in 397 cases in 2024. Sidoarjo Regency (74 cases), Surabaya City (68 cases), and Blitar Regency (66 cases) recorded the highest cumulative case counts. Spatial overlay analysis revealed that districts and cities classified with high population density tended to exhibit higher diphtheria case burdens, while areas with low healthy home coverage most notably Bangkalan Regency also showed elevated case counts. Conversely, Madiun City, which had the highest healthy home coverage, recorded only 7 cases throughout the study period. These findings indicate that population density and healthy home access are associated with the geographic distribution of diphtheria incidence, underscoring the need for territory-based, multi-sectoral prevention and control strategies in high-risk districts.